Supplementation with Branched-Chain Amino Acids Induces Unexpected Deleterious Effects on Astrocyte Survival and Intracellular Metabolism with or without Hyperammonemia: A Preliminary In Vitro Study - Ting Wang; Kazuyuki Suzuki; Toshimi Chiba; Keisuke Kakisaka; Yasuhiro Takikawa (International Journal of Hepatology)
Introduction. Ammonia is a key component in the pathogenesis of hepatic encephalopathy. Branched-chain amino acids (BCAA) have been reported to improve the symptoms of HE induced by hyperammonemia; however, we recently reported that ammonia increases intracellular levels of BCAA and exerts toxic effects on astrocytes. Objectives. This follow-up study was designed to confirm the direct effects of BCAA on human astrocytes and clarify their underlying mechanisms using metabolome analysis and evaluation of associated signaling. Methods. We performed cytotoxicity and cell proliferation tests on astrocytes following BCAA treatment with and without ammonium chloride (NH4Cl) and then compared the results with the effects of BCAA on hepatocytes and neurons. Subsequently, we used metabolomic analysis to investigate intracellular metabolite levels in astrocytes with and without BCAA treatment. Results. The astrocytes showed increased leakage of intracellular lactate dehydrogenase and reduced proliferation rate upon BCAA treatment. Interestingly, our analysis showed a BCAA-induced impairment of intracellular glycolysis/glyconeogenesis as well as amino acid and butyric acid metabolism. Furthermore, BCAA treatment was found to cause decreased levels of Glut-1 and phosphorylated GSK-3β and mTOR in astrocytes. Conclusions. Although further investigations of the effect of BCAA on human astrocytes with hyperammonemia are needed, our work demonstrates that BCAA supplementation has direct negative effects on astrocyte survival and intracellular metabolism.